Knot in my backyard - Marks, Mary (Marks, Mary. Quilting mystery., 2014)
When she stumbles over the body of baseball coach Dax Martin, middle-age divorcee Martha Ross and her fellow quilters must piece together the clues to figure out who in their neighborhood wanted the coach benched permanently.